Is Better Standardization of Therapeutic Antibody Quality in Emerging Diseases Epidemics Possible? - Ravlić, Sanda; Hećimović, Ana; Kurtović, Tihana; Ivančić Jelečki, Jelena; Forčić, Dubravko; Slović, Anamarija; Kurolt, Ivan Christian; Mačak Šafranko, Željka; Mušlin, Tatjana; Rnjak, Dina; Jakšić, Ozren; Sorić, Ena; et al. (Frontiers in Immunology, 2022)
During the ongoing COVID-19 epidemic many efforts have gone into the investigation of the SARS-CoV-2–specific antibodies as possible therapeutics. Currently, conclusions cannot be drawn due to the lack of standardization in antibody assessments. Here we describe an approach of establishing antibody characterisation in emergent times which would, if followed, enable comparison of results from different studies. The key component is a reliable and reproducible assay of wild-type SARS-CoV-2 neutralisation based on a banking system of its biological components - a challenge virus, cells and an anti-SARS-CoV-2 antibody in-house standard, calibrated to the First WHO International Standard immediately upon its availability. Consequently, all collected serological data were retrospectively expressed in an internationally comparable way. The neutralising antibodies (NAbs) among convalescents ranged from 4 to 2869 IU mL-1 in a significant positive correlation to the disease severity. Their decline in convalescents was on average 1.4-fold in a one-month period. Heat-inactivation resulted in 2.3-fold decrease of NAb titres in comparison to the native sera, implying significant complement activating properties of SARS-CoV-2 specific antibodies. The monitoring of NAb titres in the sera of immunocompromised COVID-19 patients that lacked their own antibodies evidenced the successful transfusion of antibodies by the COVID-19 convalescent plasma units with NAb titres of 35 IU mL-1 or higher.